Effect of Dopamine Transporter Gene (SLC6A3) Variation on Dorsal Anterior Cingulate Function in Attention-Deficit/Hyperactivity Disorder - Brown, Ariel B. (2010)
Objective - Although Attention-Deficit/Hyperactivity Disorder (ADHD) is associated both with brain alterations in attention and executive function (EF) circuitry and with genetic variations within the dopamine system (including the dopamine transporter gene [SLC6A3]), few studies have directly investigated how genetic variations are linked to brain alterations. We sought to examine how a polymorphism in the 3’ untranslated region (UTR) of SLC6A3, associated with ADHD in meta-analysis, might contribute to variation in dorsal anterior cingulate cortex (dACC) function in subjects with ADHD. Method - We collected fMRI scans of 42 individuals with ADHD, all of European descent and over the age of 17, while they performed the Multi-Source Interference Task (MSIT), a cognitive task shown to activate dACC. SLC6A3 3’ UTR variable number tandem repeat (VNTR) polymorphisms were genotyped and brain activity was compared for groups based on allele status. Results - ADHD individuals homozygous for the 10R allele showed significant hypoactivation in the left dACC compared to 9R-carriers. Exploratory analysis also showed trends toward hypoactivation in the 10R homozygotes in left cerebellar vermis and right lateral prefrontal cortex. Further breakdown of genotype groups showed similar activation in individuals heterozygous and homozygous for the 9R allele. Conclusions - Alterations in activation of attention and EF networks found previously to be involved in ADHD are likely influenced by SLC6A3 genotype. This genotype may contribute to heterogeneity of brain alterations found within ADHD samples.